Ta’rib di dalam al-Quran menurut Mazhab al-Imam Jalaludin as-Suyuty - Murdiono Murdiono (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2020)
This study aims at finding out non-Arabic vocabulary in the Qur'an and the perspectives of one of the most authoritative classical Qur’anic scholar, Imām as-Suyūtī on the discourse. Although the Qur'an was revealed to all mankind, the language it employs is Arabic. Even so, there are so many (perceived) non-Arabic vocabularies used in conveying the messages of the Almighty. This phenomenon has attracted the attentions of researchers to study the non-Arabic vocabularies used by the Qur’an which is called muʻarrab. The taʻrīb, the word from which muʻarrab is derived, refers to a process of formation of words in Arabic after being transferred from foreign languages. The contact the Arabs made with other people in the past can explain the emergence of muʻarrab. Amongst these people were the Persians, the Africans, the Romans, the Syrians, the Nabataeas, and others. With the contact (iḥtikāk), the Arabs found some new commodities they did not pose. They transferred new unavailable words into Arabic with some adjustments. This language phenomenon is reflected in the Qur’ān, as is confessed by as-Suyūṭī in the findings of this reseach.